EVALUASI PENERAPAN KURIKULUM MERDEKA BELAJAR MENGGUNAKAN MODEL CIPP PADA MATA PELAJARAN BIOLOGI di SMA N 1 TELAGA BIRU - Sidik Katili, Abubakar; Rusman, Rizkiyanto; Din Uno, Wirnangsi; Dama, Lilan; Maryati Yusuf, Frida; Mardin, Herinda (Jurnal Biogenerasi, 2025)
This study aimed to evaluate the implementation of the Emancipated Learning Curriculum in the Biology subject at SMA Negeri 1 Telaga Biru using the CIPP (Context, Input, Process, Product) evaluation model. The qualitative study was employed to understand the effectiveness of curriculum implementation. The evaluation of CIPP covered four aspects, encompassing context, input, process, and product. The results of the context aspect indicated that the objectives of the curriculum were in line with the school's vision and mission in shaping students' character, competitiveness, and readiness for future challenges. Then, the input aspect indicated that the readiness of teachers and adequate facilities and infrastructure, but it required improvement in technology and learning resources. In the process aspect, the learning has implemented contextual approach and project-based methods, although active student participation and access to technology were still poor. Meanwhile, the product aspect indicated an increase in learning outcomes, critical thinking skills, and deep and applicable students' conceptual understanding. In general, the Emancipated Learning Curriculum in the Biology subject has been running effectively, although continuous improvement is still needed for more optimal results.